Work from Anywhere: Treaty Shopping in Disguise? - Jarzębowska, Natalia (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The popularisation of remote work – as a result of which the concept of ‘digital nomads’ increasingly extends to office workers – makes it necessary to analyse the situation of ‘digital nomads’ from the perspective of their taxation. The cross-border situation of remote workers is analysed in this paper in the light of the provisions of double tax treaties and tax avoidance measures. The paper attempts to answer the question of what tax consequences are associated with performing work from abroad and whether the current state of international tax law allows for work to be performed from anywhere.